2008
DOI: 10.1039/b813375a
|View full text |Cite
|
Sign up to set email alerts
|

Helical nonracemic tubular coordination polymer gelators from simple achiral molecules

Abstract: A novel class of helical nonracemic tubular coordination polymers, which can immobilize a wide range of solvents at very low concentrations, have been synthesized for the first time in the absence of chiral influences and appended groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
85
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 48 publications
1
85
0
3
Order By: Relevance
“…The helical structure obtained from the achiral molecule was possible an occurrence of statistical fluctuations in the intermolecular self-assembly process, which could lead to an accidental excess of one helical direction [15][16][17][18]. After one helical direction was formed, the new aggregates would follow to form a helical secondary structure along with the same direction by chiral autocatalysis [14]. This helical structure self-assembled by achiral molecules was usually accompanied by chance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The helical structure obtained from the achiral molecule was possible an occurrence of statistical fluctuations in the intermolecular self-assembly process, which could lead to an accidental excess of one helical direction [15][16][17][18]. After one helical direction was formed, the new aggregates would follow to form a helical secondary structure along with the same direction by chiral autocatalysis [14]. This helical structure self-assembled by achiral molecules was usually accompanied by chance.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the compound 1 was an achiral molecule. Yuan et al [13] and Zhang et al [14] had reported chiral molecular assemblies from achiral amphiphilic imidazole-based ligand with AgNO 3 in gel state a) Heated to dissolve and cooled to room temperature then aged for 15 min (25°C). b) The amount of tartaric acid was 0.5 eq of 1.…”
Section: Resultsmentioning
confidence: 99%
“…间二咪唑苯本身也可以直接用于构筑新颖的功能性材 料. 例如: 其与金属钴或锌配位可以形成三维的金属有 机框架材料(MOFs) [10,11] ; 与锰和铜配位可以构建有机-无机杂化配位复合物 [12] ; 与银配位可以获得一种非消 旋的管状配位聚合物凝胶 [13] . 咪唑是一种稳定的五元缺电杂芳环, 具有吸电子效 应.…”
unclassified
“…[19] b) Selbstorganisation von Koordinationspolymergelen. [20] gelen mit Nanoröhrenstrukturen wurde durch You und Mitarbeiter beschrieben (Abbildung 3 b). [20] Das faserförmige 3D-Netzwerk wurde aus Ag + -Ionen und Imidazolderivaten synthetisiert.…”
unclassified
“…[20] gelen mit Nanoröhrenstrukturen wurde durch You und Mitarbeiter beschrieben (Abbildung 3 b). [20] Das faserförmige 3D-Netzwerk wurde aus Ag + -Ionen und Imidazolderivaten synthetisiert. In einer bemerkenswerten Synthese setzten Tang und Mitarbeiter ein Metallogel aus Ag + -Ionen und einem organischen Liganden als Templat ein, um Polyacrylamid-Nanoröhren zu erhalten.…”
unclassified